2016
DOI: 10.1103/physrevx.6.031014
|View full text |Cite
|
Sign up to set email alerts
|

All-Optical dc Nanotesla Magnetometry Using Silicon Vacancy Fine Structure in Isotopically Purified Silicon Carbide

Abstract: We uncover the fine structure of a silicon vacancy in isotopically purified silicon carbide (4H-28 SiC) and reveal not yet considered terms in the spin Hamiltonian, originated from the trigonal pyramidal symmetry of this spin-3/2 color center. These terms give rise to additional spin transitions, which would be otherwise forbidden, and lead to a level anticrossing in an external magnetic field. We observe a sharp variation of the photoluminescence intensity in the vicinity of this level anticrossing, which can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
175
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(187 citation statements)
references
References 50 publications
5
175
0
7
Order By: Relevance
“…Thus, our methods are suitable for sub-mT dc vector magnetometry. When B 0 ∼ h2D=gμ B , the suggested methods may not be useful because of complex spectra arising due to interactions among spin sublevels [56][57][58]. At high magnetic fields, e.g., B 0 ∼ 300 mT, two transitions f 21 and f 43 are well observable at every orientation as experimentally reported [17,43].…”
Section: Resultsmentioning
confidence: 92%
“…Thus, our methods are suitable for sub-mT dc vector magnetometry. When B 0 ∼ h2D=gμ B , the suggested methods may not be useful because of complex spectra arising due to interactions among spin sublevels [56][57][58]. At high magnetic fields, e.g., B 0 ∼ 300 mT, two transitions f 21 and f 43 are well observable at every orientation as experimentally reported [17,43].…”
Section: Resultsmentioning
confidence: 92%
“…The V2 line in 4H -SiC [4] and the V2 and V3 lines in 6H -SiC [13] are sufficiently strong to observe their corresponding electron spin via optically detected magnetic resonance (ODMR) measurements at room temperature. In particular, it has been demonstrated that the V2 color center in 4H -SiC can be used for magnetometer [17][18][19][20] and nanoscale thermometer [21] applications and as a room-temperature maser [14].Today, it is widely accepted that V1-V3 PL lines and T V1 -T V3 electron paramagnetic resonance (EPR) signals in 4H -and 6H -SiC are related to spin-3/2 negatively charged silicon vacancies [22][23][24][25]. On the other hand, the actual microscopic configuration of these vacancy related centers is still debated.…”
mentioning
confidence: 99%
“…The V2 line in 4H -SiC [4] and the V2 and V3 lines in 6H -SiC [13] are sufficiently strong to observe their corresponding electron spin via optically detected magnetic resonance (ODMR) measurements at room temperature. In particular, it has been demonstrated that the V2 color center in 4H -SiC can be used for magnetometer [17][18][19][20] and nanoscale thermometer [21] applications and as a room-temperature maser [14].…”
mentioning
confidence: 99%
“…Недавно нами были обнаружены вакансионные спиновые центры в карбиде кремния (SiC), в которых спиновые уровни с S = 3/2 селективно заселяются под дейст-вием оптического излучения в ближнем ИК-диапазоне, совместимом с полосой прозрачности волоконной оптики и биологических систем, и предложен способ использования оптически детектируемого магнит-ного резонанса (ОДМР) для измерения магнитных и температурных полей [2][3][4][5][6][7][8][9]. Был предложен оптический квантовый термометр [8], ко-торый использовал физическое явление сильного изменения интенсив-ности фотолюминесценции (ФЛ) (photoluminescence, PL) в магнитных полях, близких к точке антипересечения спиновых подуровней центров с S = 3/2 (level anticrossing -LAC) в возбужденном состоянии, которые характеризовались сильной зависимостью расщепления тонкой структуры (zero-field splitting) от температуры [7].…”
unclassified